Clinical inertia and treatment intensification among patients with type ii diabetes mellitus at Debre Tabor comprehensive specialized hospital, Ethiopia: an institutional-based cross-sectional study - Dagnew, Samuel Berihun; Wondm, Samuel Agegnew; Yitayew Tarekegn, Getachew; Kassaw, Abebe Tarekegn; Moges, Tilaye Arega (Frontiers in Endocrinology, 2025)
BackgroundPeople with type 2 diabetes mellitus who have clinical inertia often struggle to control their blood sugar levels and do not receive timely treatment intensification. Strict glycemic control has advantages, but many patients with diabetes are unable to reach their target blood sugar levels. The study’s main objective was to determine the prevalence of clinical inertia in patients with type 2 diabetes at Debre Tabor Comprehensive Specialized Hospital(DTCSH) in Ethiopia.MethodsAn institutional based, cross-sectional research design was used at Debre Tabor Comprehensive Specialized Hospital from November 20/2023 to January 30/2024. A structured questionnaire modified from various medical records and literatures were used to gather data. A logistic regression model was also employed after the Hosmer-Lemeshow goodness-of-fit test was checked to find contributing variables to clinical inertia. A threshold of p < 0.05 was considered statistically significant.ResultIn total, 287 samples were included in the research. The occurrences of clinical inertia 31.4% (95%CI: 25.9 - 36.8) were obtained from 90 patients. Aged patients (AOR = 1.103; 95% CI, 1.034 - 1.176; P = 0.003), medication fee (AOR = 4.955; 95% CI, 1.284 - 14.127; P = 0.020), medication nonadherence (AOR = 4.345; 95% CI, 2.457 - 15.537; P = 0.001), increase number of medication (AOR = 4.205; 95% CI, 2.657- 6.655; P ≤ 0.001), poor glycemic control (AOR = 2.253; 95% CI, 1.673 - 3.033; P ≤ 0.001) were more likely to have clinical inertia.ConclusionOne-third of patients experienced clinical inertia. Age, glycemic control, medication non-adherence, treatment fee, and number of medications were found to be strongly correlated with clinical inertia. More precise knowledge of the clinical inertia and the associated therapies is necessary to tackle this issue more effectively.